Effects of acupuncture at limb Acupoints-Guangming (GB37) on UDVA, CS, and EEG microstate in myopia - Wang, Zhongqing; Yan, Hao; Su, Kangna; Wu, Ruixin; Wang, Lihan; Bi, Hongsheng; Wu, Jianfeng (Frontiers in Neuroscience, 2024)
IntroductionAcupuncture is beneficial in improving visual function for myopi periocular acupoints Taiyang can improve contrast sensitivity (CS). In this study, we aim to further investigate the impact of acupuncture at the limbs acupoints-Guangming(GB37) acupoint on visual function, and the neural mechanism of acupuncture at the GB37 acupoint improving visual function through electroencephalography (EEG) microstate.MethodsA total of 22 myopia were recruited. Uncorrected distance visual acuity (UDVA) and CS of myopic patients were tested before and after acupuncture, and EEG data were recorded throughout the entire acupuncture procedure.ResultsOur study found that compared with pre-acupuncture, the UDVA and CS of both eyes at each spatial frequency were improved; compared with the resting state of pre-acupuncture, the duration, occurrence and contribution of microstate A were significantly increased, while those of microstate D were decreased during the post-acupuncture state. The duration of microstate A was positively correlated with the CS. There was no correlation between UDVA and EEG microstates.DiscussionAcupuncture at GB37 can improve the UDVA and CS in myopic patients, which may be related to microstate A.